Effects of nitriding and shot peening treatments and stress concentration on the fatigue strength of AISI 4340 steel - Siqueira, Célio P. (2001)
Nitriding is a thermochemical surface treatment applied to improve the fatigue and wear resistances of mechanical components. Shot peening is a cold work process in which small spheres impact the surface of a piece, producing small dimples due to superficial fibbers yielding by tension and producing a compressive residual stresses field below the dimples. Many of the material fractures are caused by fatigue as a result of inadequate projects, involving stress concentrations, or from any notch produced during process of manufacture or maintenance from equipment. The aim of this study was to analyse the effects of nitriding and shot peening surface treatments, as well as stress concentrations induced to simulate machining errors, on the rotating bending fatigue behaviour of AISI 4340 high strength steel. Copyright © 2001 Society of Automotive Engineers, Inc.